Interpretasi Ayat-Ayat Tartil dalam al-Qur’an sebagai Landasan Etika Membaca: Studi Tafsir Tematik - M. Ihsanun Mubarok; Moh. Bakir (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
This study aims to reconstruct the concept of tartīl in the Qur’an, which has often been narrowly understood as a slow and rule-based recitation method. This research employs a qualitative approach using a thematic exegesis (tafsīr maudhu‘ī) method by analyzing Qur’anic verses related to tartīl, ḥaqqa tilāwatih, and the prohibition of hastened recitation. The primary data source is the Qur’an, supported by classical and contemporary exegetical literature.The findings reveal that tartīl is a multidimensional concept encompassing four main dimensions: linguistic (phonetic accuracy), cognitive (comprehension), spiritual (internalization), and performative (ethical recitation). Furthermore, tartīl functions as a method of internalizing revelation that connects recitation with the process of tadabbur (deep reflection).This study concludes that tartīl is not merely a technical recitation method but an ethical framework for engaging with the Qur’an. The contribution of this research lies in proposing an integrative paradigm of tartīl that is relevant for recitation practices, Qur’anic education, and contemporary tafsir studies.